Karyotypic study on Silene, section Lasiostemones species from Turkey - (:unkn) unknown (FIRENZE UNIV PRESS, 2009)
Karyology of the eight taxa of section Lasiostemones from Turkey was investigated. Diploid chromosome numbers and the basic chromosome number of the studied taxa were obtained as 2n=24 and x=12 respectively. The karyotype analysis of studied taxa was carried out and chromosome number of S. capitellata, S. lasiantha and S. manissadjianii were determined at the first time. The largest chromosomes were observed in S. capitellala and the smallest ones were observed in S. isaurica. S. capitellata shows the highest A, index. S. olympica represents the highest interchromosomal asymmetry coefficient (A(2)). The karyologic results of the study and the analysis of chromosomal morphology of each taxon were shown as tables.
Keywords: caryophyllaceae; Karyology; Karyotype; Lasiostemones; Silene; SOUTH ANATOLIA; EAST ANATOLIA; CARYOPHYLLACEAE; TAXA